Formal and informal human milk donation in New Zealand: a mixed-method national survey - Shalee Harris; Frank H. Bloomfield; Mariana Muelbert (BMC, 2024)
Abstract Background Mother's milk provides optimal nutrition for infants. Donor human milk (DHM) is recommended for low birthweight infants when mother's milk is unavailable. Little is known about human milk (HM) donation practices in New Zealand (NZ), where few HM banks are available. This study aimed to investigate parents' and health professionals' (HP) experiences with formal and informal HM donation in NZ. Methods Two electronic surveys were disseminated in 2022 to parents and HPs involved with HM donation in NZ. The surveys covered respondents' views and experiences with HM donation. HPs were also asked about HM donation practices in their workplace. Chi-squared and Fisher-Freeman-Halton exact tests were used for quantitative analysis and qualitative data were thematically analysed using inductive approach. Results A total of 232 HP and 496 parents completed the surveys. Most parents either donated (52%) or sought DHM (26%) for their infant and most donations were informal, arranged between individuals (52%) or through hospital staff (22%). HP reported DHM was used in 86% of facilities, with only 20% of donations facilitated by HM banks. Almost half (48%) of HP stated they would like to use DHM in their workplace but access was limited. The most common screening processes undertaken by parents and HP before informal HM donation were lifestyle including smoking status, medication, drug and alcohol intake (44% and 36%, respectively) and serological screening such as CMV, HIV, Hepatitis C or B (30% and 39%, respectively). Pasteurisation of DHM obtained informally was not common. Most donors were satisfied with their HM donation experiences (informal and/or formal, 91%) and most respondents supported use of DHM in hospitals and community. Participants reported HM donation could be improved (e.g., better access) and identified potential benefits (e.g., species-specific nutrition) and risks (e.g., pathogens) for the infant. Potential benefits for the donor were also identified (e.g., altruism), but respondents acknowledged potential negative impacts (e.g., cost). Conclusion Informal HM donation in NZ is common. Most parents and HP support the use of DHM; however, improvements to current practices are needed to ensure safer and more equitable access to DHM.